2004
DOI: 10.1074/jbc.m310738200
|View full text |Cite
|
Sign up to set email alerts
|

A Predicted Amphipathic Helix Mediates Plasma Membrane Localization of GRK5

Abstract: G protein-coupled receptor kinases (GRKs) specifically phosphorylate agonist-occupied G protein-coupled receptors at the inner surface of the plasma membrane (PM), leading to receptor desensitization. GRKs utilize a variety of mechanisms to bind tightly, and sometimes reversibly, to cellular membranes. Previous studies demonstrated the presence of a membrane binding domain in the C terminus of GRK5. Here we define a mechanism by which this short C-terminal stretch of amino acids of GRK5 mediates PM localizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 29 publications
5
75
1
Order By: Relevance
“…The N-terminal helices of regulator of G protein signaling 2 and Rho guanine nucleotide dissociation inhibitor 3 can direct these proteins to the plasma membrane and Golgi complex, respectively (7,13). A C-terminal helix mediates the plasma membrane localization of G protein-coupled receptor kinase 5 (46). All these helices are also able to mediate the targeting of GFP, although the relocalization can be only partial.…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal helices of regulator of G protein signaling 2 and Rho guanine nucleotide dissociation inhibitor 3 can direct these proteins to the plasma membrane and Golgi complex, respectively (7,13). A C-terminal helix mediates the plasma membrane localization of G protein-coupled receptor kinase 5 (46). All these helices are also able to mediate the targeting of GFP, although the relocalization can be only partial.…”
Section: Discussionmentioning
confidence: 99%
“…GRK5 possesses an amphipathic helix in its C terminus (44), whereas the GRK6A splice variant in addition to this helix also has palmitoylation sites (45)(46)(47). In contrast, the recruitment of GRK2 and GRK3 to the membrane is believed to depend on the interaction of their pleckstrin homology domain with G␤␥ released upon G protein activation (48,49).…”
Section: Agonist-independent Receptor Phosphorylation Is Not Inhibitementioning
confidence: 99%
“…This was somewhat unexpected since alanines would not be expected to disrupt the hydrophobicity of this face. In fact, others have also reported that alanine substitutions in the hydrophobic faces of other amphipathic helices can change their properties (25). Another possibility is that the hydrophobic face of the JSRV amphipathic helix could interact with hydrophobic regions of the same or other proteins within the lipid bilayer.…”
mentioning
confidence: 99%